Corporate Governance and Fraud Prevention in Indonesian Islamic Banks - Mardiaton Mardiaton; Amru Usman; Rayyan Firdaus; Rimal Mahdani; Murni Murni (Universitas Islam Negeri Ar-Raniry, 2026)
The rapid growth of Islamic banking in Indonesia has increased the importance of strengthening governance and fraud prevention mechanisms within Islamic financial institutions. Alongside the expansion of Islamic Commercial Banks, concerns regarding fraud and deviations from Sharia principles have also become more prominent. This study aims to examine the influence of the audit committee, internal control, and Sharia compliance on fraud in Islamic Commercial Banks in Indonesia listed with the Financial Services Authority (OJK) during the 2021–2023 period. The study employs a quantitative approach using secondary data obtained from annual reports and Good Corporate Governance reports. The sample consists of 13 Islamic Commercial Banks observed over three years, resulting in 39 observational data points selected through a saturated sampling technique. Data analysis was conducted using panel data regression with EViews 12 software. The findings indicate that the audit committee has a negative and significant effect on fraud, suggesting that stronger supervisory functions contribute to reducing fraudulent practices within Islamic banking institutions. Meanwhile, internal control and Sharia compliance measured through the Profit-Sharing Ratio demonstrate positive but insignificant effects on fraud. These results imply that formal control systems and compliance indicators alone may not effectively minimize fraud risk without strong implementation, supervision, and organizational integrity. The study highlights the importance of strengthening governance quality, supervisory effectiveness, and ethical practices in supporting fraud prevention within Islamic Commercial Banks in Indonesia. ABSTRAK - Tata Kelola Perusahaan dan Pencegahan Fraud pada Bank Syariah di Indonesia. Pertumbuhan perbankan syariah di Indonesia yang terus meningkat memperkuat urgensi penerapan tata kelola yang efektif serta mekanisme pencegahan fraud pada lembaga keuangan syariah. Seiring berkembangnya Bank Umum Syariah, potensi kecurangan dan penyimpangan terhadap prinsip-prinsip syariah juga menjadi isu yang semakin relevan. Penelitian ini bertujuan untuk menganalisis pengaruh komite audit, internal control, dan syariah compliance terhadap fraud pada Bank Umum Syariah yang terdaftar di Otoritas Jasa Keuangan (OJK) selama periode 2021–2023. Penelitian menggunakan pendekatan kuantitatif dengan data sekunder yang bersumber dari laporan tahunan dan laporan Good Corporate Governance Bank Umum Syariah. Sampel penelitian mencakup 13 Bank Umum Syariah yang diamati selama tiga tahun, sehingga diperoleh 39 observasi penelitian dengan teknik sampel jenuh. Analisis data dilakukan menggunakan regresi data panel dengan bantuan perangkat lunak EViews 12. Hasil penelitian menunjukkan bahwa komite audit berpengaruh negatif dan signifikan terhadap fraud, yang mengindikasikan bahwa peran pengawasan yang efektif mampu menekan tingkat kecurangan dalam perbankan syariah. Sebaliknya, internal control dan syariah compliance yang diukur melalui Profit Sharing Ratio menunjukkan pengaruh positif namun tidak signifikan terhadap fraud. Temuan ini mengisyaratkan bahwa keberadaan sistem pengendalian dan indikator kepatuhan syariah secara formal belum tentu efektif dalam menurunkan risiko fraud tanpa didukung oleh implementasi yang konsisten, pengawasan yang optimal, serta integritas organisasi. Oleh karena itu, penguatan tata kelola, efektivitas pengawasan, dan penanaman nilai etika menjadi aspek penting dalam upaya pencegahan fraud pada Bank Umum Syariah di Indonesia.